1997
DOI: 10.1002/(sici)1097-4628(19971031)66:5<901::aid-app10>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic networks. XI. Mechanical properties and morphology

Abstract: ABSTRACT:The bulk properties of two types of amphiphilic networks, poly(2-hydroxyethyl methacrylate)-l-polyisobutylene (PHEMA-l-PIB, H-network) and poly( N,N-dimethylacrylamide)-l-polyisobutylene (PDMAAm-l-PIB, A-network), have been investigated. Tensile strengths decreased considerably by swelling, and the decrease was more severe by swelling in water than in n-heptane. Elongations increased by swelling in water; however, the change was not consistent upon swelling in n-heptane. The hardness of dry networks d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 6 publications
1
34
0
Order By: Relevance
“…In many biphasic systems, 13,24 it has been identified that the magnitudes and the location of a glass transition caused by a single phase are dominated by its content. On the other hand, the compatibility of AO-80 and CPE is considerably enhanced with increasing thermal forming temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In many biphasic systems, 13,24 it has been identified that the magnitudes and the location of a glass transition caused by a single phase are dominated by its content. On the other hand, the compatibility of AO-80 and CPE is considerably enhanced with increasing thermal forming temperature.…”
Section: Resultsmentioning
confidence: 99%
“…(5) in Section 3 as the product of the surface tension between water and the hydrophobic units, g, times the hydrophobic interfacial area S cylinder interfacial : Again, g is provided by Eq. (6).…”
Section: Discussionmentioning
confidence: 99%
“…This structure leads to swelling in both aqueous and organic media [2], and adsorption of both hydrophilic and hydrophobic solutes [3,4]. Moreover, there is a growing body of evidence for the microphase separation of CSACPNs both in water and in organic solvents, but particularly in water [5,6]. The main application of these materials is drug delivery, with the use of CSACPNs both as drug release matrices [3,4] and as semi-permeable membranes [7].…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Transmission electron microscopy of a typical amphiphilic network has shown 20-50-Å -diameter bicontinuous domains with a salt-and-pepper morphology.…”
Section: Smart Amphiphilic Hydrogelsmentioning
confidence: 99%